Islamic Education in the Shadow of Nipponization Policy (1942-1945): a Historical Perspective - Ajmain, Maftuh (International Journal of Applied Educational Research (IJAER), 2024)
Japan came to Indonesia and ruled for about three years. Although the period of occupation was relatively short compared to the Netherlands which ruled for hundreds of years, Japan succeeded in issuing and implementing its political policies. One of the most important of these policies was nipponization. Using historical methods, this paper traces the influence of the nipponization policy on the existence of Islamic education. It was found that during the Japanese occupation, Islamic education became increasingly vibrant in various regions. Religious education was also included in the curriculum of government schools from elementary to tertiary levels. This was due to Japan's friendlier attitude towards Muslims. However, this policy was not accompanied by the availability of teachers, so religious subjects did not work properly